Re-aktualisasi Tato pada Iklan A Mild “You Will Figure It Out” dalam Membentuk Positioning Produk - Aisyi Syafikarani (DeKaVe, 2018)
Abstract.Indonesia has a variety of cultures that produce works of art and one of them is a tattoo. The oldest tattoos in Indonesia are those owned by the Mentawai and Dayak tribes. But in its development the meaning of tattoos has been re-actualized into bad value. The shift in interpretation of tattoo stigma is used by A Mild to shape the positioning of its products in the minds of consumers. A Mild "You Will Figure it Out" took an extreme step, choosing to lift the identity of young minorities who were considered one eye, one of which was the character of a young tattooed person.The ad visualization study will be analyzed using descriptive qualitative methods. The analysis will be divided into two stages, first stage is analyzing audio visual elements in advertisements, namely hear words, color, music, picture, seen words and movement. As well as analyzing filmic dramatiology with cinematographic theory which includes the camera's point of view, image size, lighting and settings. Then in the second stage, it is analyzing the shift of interpretation using the semiotic approach which refers to Roland Barthes's theory. Thus, this study can provide knowledge and insights about advertising and the development of design science, in the form of the application of analysis and criticism of the meaning in advertising, especially in the formation of product interpretation and positioning.Keywords:tattoos, re-actualization, cigarettes, semiotics, advertising